Impact study on aircraft type laminate composite plate: experimental, failure criteria and element model review - Aminanda, Yulfian (Springer - Verlag, 2012)
This paper reviews the advancement of study of composite laminate subjected to impact loading for aerospace application such as Glass fiber-epoxy and Carbon fiber-epoxy unidirectional laminate plate. The impact testing set-up and equipments are overviewed in this paper including the calculation to obtain the force, velocity and energy absorbed by the laminate during impact. The initial damage can be explained by the threshold of energy absorption while the successive damage mechanism can be described by the drop of force obtained from the history of force during impact. The corresponding evidence of damage related to force drop shows the scenario of damage mechanism; matrix cracking, delamination and fiber failure. The influence of projectile and laminate parameters to the impact behavior is reviewed as well. The failure criteria for each phase of damage mechanism are described in detail. The proposed elements model to simulate the damage are overviewed as well, which can be divided into two categories; element without interface layer and with interface layer integrating degradation of mechanical properties. The exposed failure criteria and elements model are the basis of today’s development of FEA simulation for impact purpose.